Motif dan Kepuasan Penggunaan Media Sosial Instagram terhadap Mahasiswa Fakultas Hukum Universitas Medan Area - Diana Azhary Nasution; Nina Siti Salmaniah Siregar; Rehia K.Isabela Barus (Universitas Medan Area, 2022)
The title of this research in the Motives and Satisfaction of Using Instagram Social Media for Students of the Faculty of Law, University of Medan Area. As the purpose of thus study is to test how much motivation and satisfaction in the use of social media Instagram on the use of student. The method used is to use a quantitative descriptive research methodology. Withdrawal of samples using the chi-square correlation test to determine the relationship or influence of two nominal variables and to measure the strength of the relationship or influence between motive and satisfaction. Based on the results of the research conducted, it was found that the influence of the information motive on the satisfaction of using Instagram social media on students of the Faculty of Law, Medan Area University showed a p value of 0.002 that there was an influence between information motives and satisfaction using Instagram, then personal identity motives and satisfaction using social media Instagram showed p value 0.015 that there is an influence between the motive of personal identity and the satisfaction of using Instagram, then the motive of integrity and social interaction with the satisfaction of using social media Instagram shows a p value of 0.005 that there is an influence between the motive of integrity and social interaction with the satisfaction of using Instagram, and test results Chi-square on entertainment motives with satisfaction in using social media Instagram shows a p value of 0.000 that there is an influence between entertainment motives and satisfaction in using Instagram. The value of the relationship between entertainment motives and the satisfaction of using Instagram is 0,000, which means that the influence of entertainment motives and the decision to use Instagram is significant, the chi-square test results show that the satisfaction of using Instagram social media on entertainment motives is 73%.